Tinjauan Etika Bisnis Islam dalam Corporate Social Responsibility PT. Garudafood Kabupaten Pati - Alif Arfiansyah (ITB AAS INDONESIA Surakarta, 2020)
Corporate Social Responsibility (CSR) is a positive image for companies to stakeholders in a business. Business ethics is very necessary, because business ethics is a values about good, bad, right and wrong in business. Meanwhile, business ethics in Islam like trust, fairness and honesty are essential elements in achieving the success of a business. CSR of PT.Garudafood is realized through Garudafood Sehati which is focused on social activities. The research objectives are to explain 1) Islamic business ethics; 2) CSR; and 3) CSR management of PT GarudaFood in Islamic business ethics. This research is a qualitative research. Primary data obtained from interviews and documentation. Secondary data were obtained from books and internet sites containing economics, Islamic business ethics, and CSR. The results of this study are 1) Islamic business ethics has basic axioms, namely unity, equilibrium, free will, benevolence, responsibility, shiddiq, istiqamah, fathanah, amanah, and tablig. 2) PT. Garuda Food has got CSR in the social, economic, and environmental fields. 3) The application of a form of social responsibility in accordance with Islamic business ethics, namely a form of business responsibility between man and God, man and the universe, and man and man.